Märchenadaptionen in Romanen und Novellen von Christoph Martin Wieland zu Thomas Mann - Eine exemplarische Untersuchung - Yang, Zhizi (Universitätsverlag Göttingen, 2018)
This work deals with intertextual theories and investigates narrative texts (by Wieland, Novalis, Chamisso, Storm, Andersen and Thomas Mann) from the Enlightenment of the 18th century to Classical Modernism of the early 20th century. In addition to the fairytale requisites, the less obvious fairytale-like text structures, which show a connection between different literary genres (novella/novel and fairytale) and a confrontation between the fairytale-like and the fictitious-realistic, will also be examined. The relationship between the writing process of fairytale adaptation and literary modernity - a literary modernity that reflects a social modernity characterized by its social ambivalence and plurality (modernity as a macro epoch after Anke Lohmeier and Dirk von Petersdorff) - will be shown. The six narrative texts - Die Abentheuer des Don Sylvio von Rosalva, Die Lehrlinge zu Sais, Peter Schlemihls wundersame Geschichte, Der Schimmelreiter, Peer im Glück (as an excursion and outlook into contemporary European literature) and Königliche Hoheit - with their diversity of layers of meaning are regarded as modern narrative texts and represent various milestones in the development of the concept of modernity.